Kontrak Kerja Serta Perlindungan Hukum Hak dan Kewajiban Pekerja dalam Sistem Ketenagakerjaan di Indonesia - Nirwana, Rena Putri; Damayanti, Ratih (Media Hukum Indonesia (MHI), 2024)
Many workers in Indonesia experience violations of legal protection of their rights and obligations, caused by their ignorance of employment contracts and the rights and obligations inherent in the workforce. This issue is the basis for this study, which aims to analyze employment contracts in the context of labor law, focusing on the legal protection of workers' rights and obligations. This study uses a qualitative method with a descriptive approach. The results of the study show that labor law is always related to the protection of workers' rights and obligations. In employment law, an employment contract is understood as a written agreement between an employee and an employer that regulates various aspects of the employment relationship between the two. This contract serves as a legal basis that protects the rights and obligations of each party. Legal protection itself is an effort to protect the dignity and human rights (HAM) owned by legal subjects, in accordance with applicable legal regulations, either in the form of policies or regulations aimed at safeguarding these interests from threats. The rights and obligations between parties are interrelated, where the rights of one party become an obligation for the other.